2022
DOI: 10.4274/jtgga.galenos.2022.2022-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and environmental mercury exposure and human reproductive health - a review

Abstract: Mercury is a toxic heavy metal. Humans are exposed to mercury through several sources including environmental, occupational, contaminated food and water and from mercury-containing dental amalgam. Mercury exposure is known to harm the nervous system profoundly, and have a negative impact on digestive and immune systems, and other organs. To review and discuss the effect of mercury exposure through environmental or occupational routes on human reproduction, pregnancy, and its outcome. Published information abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…In studies using laboratory mammals, both organic and inorganic forms of mercury have demonstrated dose-dependent effects on fertility [ 50 , 51 ]. Organic methylmercury can elicit (or induce) effects on DART endpoints at lower concentrations than inorganic mercury due to its ability to cross the placenta and blood–brain barrier [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies using laboratory mammals, both organic and inorganic forms of mercury have demonstrated dose-dependent effects on fertility [ 50 , 51 ]. Organic methylmercury can elicit (or induce) effects on DART endpoints at lower concentrations than inorganic mercury due to its ability to cross the placenta and blood–brain barrier [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This C. elegans study assessed progeny to adult ratios, germline apoptosis, and germline epigenetic regulation for DMA and NaAsO 2 , along with inorganic HgCl 2 and organic meHgCl (Table 2), which have more thoroughly studied reproductive effects in mammalian models. In studies using laboratory mammals, both organic and inorganic forms of mercury have demonstrated dose-dependent effects on fertility [50,51]. Organic methylmercury can elicit (or induce) effects on DART endpoints at lower concentrations than inorganic mercury due to its ability to cross the placenta and blood-brain barrier [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is the study by Kumar, Sharma, and Sedha (2022) where male reproductive health is exposed in terms of mercury contamination, especially in the quality of semen, which, having high levels of mercury in the blood, alters the morphological percentage of spermatozoa. In the ACSe of women, there are problems in pregnancy, complications in the development of babies, alterations in the menstrual cycle and miscarriages (Kumar et 2022).…”
Section: Human Health Impactsmentioning
confidence: 99%
“…Finally, there is the study by Kumar, Sharma, and Sedha (2022) where male reproductive health is exposed in terms of mercury contamination, especially in the quality of semen, which, having high levels of mercury in the blood, alters the morphological percentage of spermatozoa. In the ACSe of women, there are problems in pregnancy, complications in the development of babies, alterations in the menstrual cycle and miscarriages (Kumar et 2022). In the study carries out by Diwa, Deocaris, Geraldo, and Belo (2022) the ecological and health impacts of heavy metals from a mercury mine are evaluated, in which the probability of adverse effects for adults and children is suggested, with an average contribution of heavy metals of 38.8% for adults and children (Diwa et al, 2022).…”
Section: Human Health Impactsmentioning
confidence: 99%
“…Bio-PVC otherwise still require similar considerations as fossil carbon-based PVC materials for the rest of their life cycle as detailed below. Production & Manufacturing Monomer production Mercury – About 50 metric tons utilised in 2020 [ 183 ] by older technologies that are still operational for chlorine production [ 184 ]; also used as a catalyst for production of vinyl chloride monomer [ 185 ] Highly hazardous chemical, classified as a reproductive toxicant [ 4 , 186 ] – released into the air, water, and landfills from mercury cell plants [ 187 ], leading to occupational exposures [ 188 ], potential exposures in fenceline communities [ 189 ], and potential health impacts, even at low levels [ 190 ]. Asbestos – About 100–800 metric tons [ 191 ] is used by older technologies for chlorine production [ 184 ] per year A carcinogen [ [192] , [193] , [194] ] – released into the air and landfills from asbestos diaphragm cell plants [ 187 ] and there is potential for occupational exposure [ 191 ].…”
Section: Polyvinyl Chloridementioning
confidence: 99%